Analisis Kegiatan P5P2RA dalam Mengembangkan Keterampilan Abad 21 - Suci Nur Rahayu; Ahmad Aziz Fanani (Tarbiyatuna Kajian Pendidikan Islam, 2025)
Education in Indonesia is undergoing a transformation to improve its quality and relevance with current developments, especially in the era of globalization in the 21st century which is marked by advances in information and communication technology. This research focuses on analyzing the suitability between the implementation of the Pancasila Student Profile Strengthening Project and Rahmatan lil 'Alamin Student Profile (P5P2RA) program at MTsN 1 Jember, with 21st century skills, including critical thinking, collaboration, communication and creativity (4C) and find out the impact of implementing the P5P2RA program on learning activities. This program combines project-based learning with Pancasila values ​​and local wisdom. Even though there have been several studies discussing similar issues, in-depth research regarding the P5P2RA program with 21/4C century skills is still limited. In this case, the researcher's position is to fill the gaps in these limitations. The research method used is qualitative with a case study approach, involving observation, interviews and document review. The results of the research show that the implementation of P5P2RA at MTsN 1 Jember is in accordance with the skills needs of the 21st century. The activity approach carried out contains activities that are in accordance with the indicators of creativity, critical thinking, communication and collaboration skills and the learning experience from the P5P2RA program can improve the quality of students' learning both in class and independent study.